Clusters, Stars, and Hashtags: Understanding Librarians' Professional Online Networks. Issue 1 (13th October 2021) - Hicks, Deborah
ABSTRACT: Twitter serves as a platform for librarians to connect with each other and discuss, debate, and find consensus around professional issues. Using Social Network Analysis and participant interviews, the Twitter conversations that coalesced around the hashtags #NoHateALA and #IStandWithALA, with particular attention to the role of central actors, are examined. Findings reveal that five Twitter accounts were responsible for 75.5% of all posts under these hashtags out of 1693 posters. In interviews, some of the central actors indicated that their centrality in these networks was deliberate and part of a larger activist agenda. Understanding the depth and breadth of the online network, alongside an understanding of how and why the central actors took on such important roles in the network sheds light on how librarians use online tools to connect and debate professional issues and effect important professional changes.